THE EMPLOYEES’ ATTITUDE TOWARDS ISO 9001:2015 QMS AT KENYATTA NATIONAL HOSPITAL, KENYA - Karume Benjamin Anyong’a; Prof. Jamin Masinde; Dr. Eric Masese (EPRA International Journal of Research and Development (IJRD), 2022)
The purpose of the study was to investigate the employees’ attitude towards ISO 9001:2015 QMS at Kenyatta National Hospital. Data was collected from 291 employees of the Hospital selected through a multistage sampling procedure, by use of self-administered questionnaires. Findings of the study revealed moderate attitude scores that were stronger on cognitive aspects and weaker on experiential aspects. The study established that there was a positive relationship between employees’ attitude and compliance with ISO 9001:2015 QMS at Kenyatta National Hospital with a Pearson r of 0.57 and P≤0.05. Key factors that influenced employees’ attitude were identified as lack of management support, inadequate tools and equipment as well as absence of a reward mechanism linked to compliance. To improve employees’ attitudes and by extension compliance with QMS, Kenyatta National Hospital needs to improve on equipment and working tools, improve management support as well as develop and implement a system of rewards and sanctions that are linked to compliance.